Strengths-Based Multicultural Counseling (SBMC) Model: An Approach for Counselors and Guidance and Counseling Teachers in the 21st Century - Rahmawati, Novi Rosita; Utomo, Prio (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2024)
The diversity among students serves as a valuable potential for fostering dynamic interactions and personal growth. To harness this potential, every student must cultivate multicultural awareness, which does not develop automatically but requires intentional efforts from an early stage. This article highlights the critical importance of strengths-based multicultural counseling and its relevance in the 21st century. The study utilizes a literature review as a methodological approach to emphasize the significance of strengths-based multicultural counseling, focusing on the opportunities and challenges faced by counselors and guidance teachers in contemporary contexts. Findings from the study reveal that strengths-based multicultural counseling is recognized as a "fourth force" or dimension within the counseling field, positioned alongside humanism, behaviorism, and psychodynamics. This approach emphasizes the need for cultural competence in counselors, encompassing the knowledge, skills, and attitudes necessary for professional practice in strengths-based multicultural counseling. Counselors are encouraged to view this method as a long-term relational process rather than a temporary intervention, given its implications for problem-solving and fostering understanding of diverse values among students. The counseling process thus becomes a